Quantitative analysis of jatropha growth: micronutrient delivery system and NPK combined effects (Bioscience Journal, 2018)
Studies approaching jatropha (Jatropha curcas L.) growth through quantitative analysis parameters are limited, especially regarding the response to different fertilizer types and doses. In order to investigate the effects of a micronutrient delivery system (MDS) fertilizer, a full quantitative analysis of growth in jatropha young plants was performed, comparing this system effectiveness under different NPK doses. Plants were grown in 3.9 L pots containing local soil, with or without MDS (main plot), combined with NPK doses (0; 1.8; 4.7 and 7.4 g L-1) in subplots. Dose-response curves of quantitative analysis variables were generated for three periods of time (40, 80 and 120 days after sown) as a sub-subplot. Quantitative analysis of growth showed that most parameters evaluated in this study were improved by MDS application, resulting in benefits for jatropha initial development, regardless of NPK doses. Even without NPK supplementation or under the lowest dose evaluated (1.8 g L-1), MDS provided better growth of J. curcas plants, being usually equivalent to the highest doses of NPK (4.7 and 7.4 g L-1) without MDS. The effective response of jatropha young plants to MDS supplementation indicates that this kind of fertilizer played a relevant role in the species metabolism, resulting in faster growth and enhanced biomass allocation.